2012
DOI: 10.3858/emm.2012.44.12.082
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the plant viral protease NIa in the brain of a mouse model of Alzheimer's disease mitigates Aβ pathology and improves cognitive function

Abstract: The plant viral protease, NIa, has a strict substrate specificity for the consensus sequence of Val-Xaa-His-Gln, with a scissoring property after Gln. We recently reported that NIa efficiently cleaved the amyloid-β (Aβ) peptide, which contains the sequence Val-His-His-Gln in the vicinity of the cleavage site by α-secretase, and that the expression of NIa using a lentiviral system in the brain of AD mouse model reduced plaque deposition levels. In the present study, we investigated whether exogenous expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…We examined whether similar changes could occur in the AD‐like brain. Tg‐APP/PS1 mice, which express high levels of Aβ in the brain at 8 months of age (Kim et al, ), showed increased expression of hypoxia‐related markers, including Hif‐1α , Hmox1 , and Pdk2 , in the hippocampus, whereas Tg‐APP/PS1 mice treated with hyperoxygenation (HO 2 ; 100% O 2 , 2 ATA) for 1 hr daily for 28 days had reduced expression of these factors (Supporting information Figure e–f).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…We examined whether similar changes could occur in the AD‐like brain. Tg‐APP/PS1 mice, which express high levels of Aβ in the brain at 8 months of age (Kim et al, ), showed increased expression of hypoxia‐related markers, including Hif‐1α , Hmox1 , and Pdk2 , in the hippocampus, whereas Tg‐APP/PS1 mice treated with hyperoxygenation (HO 2 ; 100% O 2 , 2 ATA) for 1 hr daily for 28 days had reduced expression of these factors (Supporting information Figure e–f).…”
Section: Resultsmentioning
confidence: 94%
“…To address this, Tg‐APP/PS1 mice treated with HO 2 (100% O 2 , 2 ATA), starting from 7 months of age, for 1 hr daily for 2 weeks were placed in the indicated behavioral tests while continuing HO 2 treatment on the given schedule (Figure a). Tg‐APP/PS1 mice at 7.5 months of age display severe cognitive deficits (Kim et al, ). During the training phase of the water maze test, Tg‐APP/PS1 mice given HO 2 exhibited a markedly reduced latency to find the hidden platform compared to Tg‐APP/PS1 control mice (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the plaque deposition and behavioral deficits at 6-8 months of age [45, 46], Tg-APPswe/PS1dE9 mice do not develop NFTs or neuronal loss. Tg-APPswe/PS1dE9 mice became popular partly due to the early availability from JAX (Table 1).…”
Section: App+ps Transgenic Modelsmentioning
confidence: 99%
“…In an in vitro study, we demonstrated that NIa specifically cleaves Aβ, which contains the Val-His-His-Gln sequence near to its putative α-secretase cleavage site [23]. We further showed that lentivirus-mediated expression of NIa in the brain of AD mice significantly reduced Aβ pathology and improved behavioral deficits [23], [24].…”
Section: Introductionmentioning
confidence: 82%